SEISMIC ANALYSIS ON SYMMETRIC AND ASYMMETRIC HOSPITAL BUILDING USING NBC CODE (International Journal of Food and Nutritional Sciences, 2022)
Symmetric and asymmetric structure models are very much common nowadays in rural as well as urban areas. This is due to the land scarcity problem, Increase in population, and vast increase in land cost. Due to various reasons such as; Site conditions, Barriers, operation needs, and many others, many structures cannot be regular or symmetrical in shape, size, stiffness, etc., and many more. A structure with asymmetric or irregular configuration might be designed or constructed to meet all the required codal requirements. But the behavior and performance of asymmetric or irregular structures will not be good as the symmetric and regular configurations. It is often suggested to designers and contractors to avoid such asymmetric and irregular configurations but due to various reasons, irregularity in the design and structural components might not be avoidable. This report aims to differentiate the seismic performance of two 15 Bedded Hospital buildings in Morang District, Nepal (Symmetric and Asymmetric Configuration). Models of rectangular shape (at Gramthan Rural Municipality, Morang District, Koshi Province, Nepal) and L-Shaped (at Dhanpalthan Rural Municipality, Morang District, Koshi Province, Nepal) buildings are designed and considered for analysis in Etabs 2016 software, Using NBC Code for the seismic analysis. After the analyses of these two models, various parameters such as displacement values, drift values, storey shear, base shear, overturning moment and stiffness, etc. were exported from the Etabs 2016 software and then the values were organized, analyzed, and compared. It can be concluded from the results that symmetrical shape structures have better results than asymmetric shape structures i.e. superior to asymmetric shape structures in the view of resistance.